Respuesta :
- x = 3/11
- y = -7/11
Step-by-step explanation:
y = 5x - 2…Equation 1
3x - 5y = 4…Equation 2
Subtitute value of y to Equation 2 :
3x - 5(5x - 2) = 4
3x - 25x + 10 = 4
-22x + 10 = 4
10 - 4 = 22x
6 = 22x
6/22 = x
3/11 = x
Subtitute value of x to one of Equation :
for example Equation 2…
3x - 5y = 4
3(3/11) - 5y = 4
9/11 - 5y = 4
9/11 - 4 = 5y
(9 - 44)/11 = 5y
(-35)/11 = 5y
(-35)/11 × 1/5 = y
-7/11 = y
3x - 5(5x - 2) = 4
3x - 25x + 10 = 4
-22x = 4 - 10
-22x = -6 ➗ -22
X = 3/11
3x - 25x + 10 = 4
-22x = 4 - 10
-22x = -6 ➗ -22
X = 3/11